Digital art photography for dummies - Bamberg, Matthew (--For dummies., 2006)
So you've made the jump to digital photography and you're having a ball with your new camera, right? Now, you're wondering just what it would take to make your photos a little more than just snapshots. Well, Digital Art Photography For Dummies is a great place to find out!You'll not only discover great new ideas, you'll see the effects in full color. This book will help youGet fabulous, well-exposed photos, no matter what your shooting conditions may beTweak, edit, and enhance your images to create something a lot better than what you started with, or maybe something entirely newProduce galler.